PROFIL GAYA BERKOMUNIKASI ORANG TUA DALAM KEPEMIMPINANDI LINGKUNGAN KELUARGA PADA PESERTA DIDIK KELAS VIII DI SMP N 2 BAYANG KABUPATEN PESISIR SELATAN - Rullya, Irvan (Bimbingan dan Konseling, 2014)
ABSTRACTThis research was exposed by their communication pattern of parents in educating children make any teenagers who dont care about the environment with purpose is to describe : Form  style of communicating in the leadership of the parent oteriter and form of communication in leadership style of parents of democracy. This research is a descriptive quantitative research. The population of this research is all the participants  of learners class VIII in SMP Negeri 2 Bayang  of the Pesisir Selatan district 204 people. The techniques used in the taking of the sample was proportional random sampling techniques. All of the sample  as many as 53 people. This instruments that used in this research like questionnaire. The analysis of the data used is the percentage of the formula. The results of this research revealed that: The form of a style of communicate in the leadership of authoritarian parents as many as 56,60 53 % of respondents are in the category very well. Communicate in the form of a style of leadership parents democracy as many as 49,06 53 % of respondents are on good category.